Rehabilitation practices in Macao: an overview of approaches and recent developments - Leong, Donna Soi Wan (Approaches to offender rehabilitation in Asian jurisdictions, 2024)
This chapter provides an overview of offender rehabilitation in Macao, focusing on crime trends and patterns, rehabilitation practices, and current challenges and recent developments. The chapter begins by introducing the background and context of Macao. It then examines recent crime trends and patterns, elucidating the context in which rehabilitation efforts are implemented. The current mechanisms and political contexts of offender rehabilitation are explored, along with an overview of prison-based and community-based programmes, as well as post-release services. Statistical contexts of recidivism and social reintegration in Macao are discussed. The chapter concludes by emphasising the challenges faced in achieving successful rehabilitation outcomes and highlighting the need for ongoing improvements and recent developments in Macao's rehabilitation practices.